MOU on efficient water management practices by California agricultural water suppliers - can it work? - Reynolds, Roger L., author; Slavin, Tracy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
In September 1990, AB 3616, "The Agricultural Water Suppliers Act," became law in California. This law required the Department of Water Resources (DWR) to establish an advisory committee to review and study potential Efficient Water Management Practices (EWMPs) and to determine which were feasible for achieving water conservation. The advisory committee was comprised of representatives of the California farming community, agricultural water suppliers, the Department of Food and Agriculture, the University of California, the California State University, public interest groups, and other interested parties. During 1992, the last year of California's six year drought, Governor Wilson, in a speech discussing California's water needs, referred to the many water conservation practices developed by California's farmers and expressed his support for the development of EWMPs for agricultural water use. He further emphasized the AB 3616 Advisory Committee should develop a strategy for implementing these practices. An Urban Memorandum of Understanding (MOU) had recently been signed by urban water suppliers and public interest groups (environmentalists). The urban signatories committed to implement certain Best Management Practices during a specific time frame to help reduce future demand and conserve water supplies. The Governor was hopeful a similar MOU could be developed for agricultural water suppliers which would encourage further improvements in water management. The Governor's directive changed the purpose of the AB 3616 Advisory Committee. Not only was a list of efficient water management practices to be prepared, but a document was also needed which outlined a reasonable implementation plan acceptable to both agricultural and environmental representatives. Since 1992, the Advisory Committee members have been working to develop an acceptable MOU. There have been many meetings, disagreements, and at times uncertainty over whether a workable product could be developed. The Advisory Committee approved the Final Draft MOU on October 15, 1996. Can it work and will it be effective in further improving agricultural water management or is it just another layer of bureaucracy? This paper will discuss the process followed, areas of disagreement, and what steps were taken to reach a consensus.
1996 USCID water management conference
Efficient water management practices
Not digitized by CSUL Digital Services.
Presented at Competing interests in water resources - searching for consensus: proceedings from the USCID water management conference held on December 5-7, 1996 in Las Vegas, Nevada.